SPECIFICS OF NUTRITION FOR COMBAT SPORTS ATHLETES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article highlights the importance and specifics of proper nutrition for combat sports athletes. It provides scientific data on how athletes' nutrition regimens affect their training efficiency, recovery processes, and overall health. Based on global experience and statistical data on liver diseases, suitable nutrition strategies for combat sports athletes are recommended.